Community engagement in Canadian health and social science research: Field reports on four studies - Eaton, Andrew D. (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2020)
Community engagement is a hallmark of Canadian health and social science research, yet we lack detailed descriptions of pragmatic peer engagement possibilities. People personally affected by a study’s topic can actively contribute to design, data collection, intervention delivery, analysis, and dissemination yet the nature and scope of involvement can vary based on context. The shift from academic to community-based research teams, where peers who share participant identities assume a leadership role, may be attributed to the HIV/AIDS response where community co-production of knowledge has been a fundamental component since the epidemic’s onset. This article discusses four health and social science studies from a community-based participatory research (CBPR) framework and synthesizes the strengths and limitations of community engagement across these endeavours to offer lessons learned that may inform the design of future CBPR projects.